2015
DOI: 10.1111/imm.12427
|View full text |Cite
|
Sign up to set email alerts
|

Time–course study of different innate immune mediators produced by UV‐irradiated skin: comparative effects of short and daily versus a single harmful UV exposure

Abstract: SummaryThe modulatory effects of solar UV radiation on the immune system have been widely studied. As the skin is the main target of UV radiation, our purpose was to compare the impact on skin innate immunity of two contrasting ways to be exposed to sunlight. Hairless mice were UV irradiated with a single high UV dose simulating a harmful exposure, or with repetitive low UV doses simulating short occasional daily exposures. Skin samples were taken at different times after UV irradiation to evaluate skin histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…As previously reported, UVr is able to perturb the skin barrier function , . Moreover, as shown here, UVr can also modulate the adaptive immune system, depending on the dose of radiation received.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As previously reported, UVr is able to perturb the skin barrier function , . Moreover, as shown here, UVr can also modulate the adaptive immune system, depending on the dose of radiation received.…”
Section: Resultssupporting
confidence: 80%
“…Skin exposure to an shUVd and rlUVd produces changes in the innate immune system as we have previously reported . Based on those results, we have decided to evaluate the possible effects of UVr on adaptive immunity.…”
Section: Resultsmentioning
confidence: 93%
“…These peptides have modest antimicrobial activity but rather pleiotropic immunoregulatory properties (52). They are produced in sub-erythemal UV-irradiated skin in the absence of any inflammation (53); they include cathelicidin LL-37 and the α- and β-defensins (52). As shown in a murine model, β-defensins via induction of T-regulatory cells can prevent and mitigate EAE (54).…”
Section: Proposed Mechanism Of Prevention Of Ms Development By Uvb Phmentioning
confidence: 99%
“…A recent study closely monitored molecular events instigated in the skin upon single high dose "harmful" UV exposure and upon multiple low dose "daily" exposure [71]. It was found that acute inflammation was only triggered by a single high UV dose; the response to chronic low UV doses was distinct and didn't implicate strong inflammatory signals.…”
Section: A Hint Of Protective Function: Systemic Pro-homeostatic Effementioning
confidence: 99%